2013
DOI: 10.11144/javeriana.sc18-3.rgsf
|View full text |Cite
|
Sign up to set email alerts
|

Relação entre qualidade do sono e funções cognitivas em pacientes com doença de Parkinson

Abstract: Here, we describe the clinical characteristics of patients with Parkinson's disease, as well as study the relationship between sleep quality and cognitive functions. This is a descriptive-analytical cross-sectional study in which we evaluate episodes of depression and anxiety, as well as the state of general health, disease progression, sleepiness, sleep quality and cognitive functions of 24 patients with Parkinson's disease without dementia. We found a moderate inverse correlation between memory and sleep dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…The sleep disorder symptom was present in both groups, suggesting an association between this symptom and worse performance. Studies shown that sleep is involved in learning and memory processes consolidation and concluded that sleep disorders in PD, besides reducing quality of life, cause cognitive deficits in memory, learning, and executive functions (30) . Other studies also shown that sleep disorders are more prevalent in subjects with MCI than in those without cognitive impairment, according to a review by Silva (31) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sleep disorder symptom was present in both groups, suggesting an association between this symptom and worse performance. Studies shown that sleep is involved in learning and memory processes consolidation and concluded that sleep disorders in PD, besides reducing quality of life, cause cognitive deficits in memory, learning, and executive functions (30) . Other studies also shown that sleep disorders are more prevalent in subjects with MCI than in those without cognitive impairment, according to a review by Silva (31) .…”
Section: Discussionmentioning
confidence: 99%
“…Testes Neuropsicológicos DP Controles p (26) DP (25) (n=33) DDP (n=15) GC (25) (n=28) DGC (n=16) MEEM × (dp) 27,4 (1,68) 27,4 (2,59) 27,8 (1,23) 27,3 (1,20) > 0,05 BDI × (dp) 4,3 (2,97) 14,9 (5,47) 4,8 (2,50) 17,7 (7,81) < 0,05 TMF Nomeação 10,0 (0,00) 10,0 (0,00) 9,6 (1,89) 10,0 (0,00) > 0,05 MI (1) × (dp) 5,3 (1,43) 5,1 (1,51) 5,6 (1,13) 5,5 (0,89) > 0,05 M1 (2) × (dp) 7,5 (1,37) 7,4 (0,91) 8,4 (1,20) 8,1 (1,30) < 0,05 M2…”
Section: Tabela 6: Desempenho Dos Grupos Nos Testes Neuropsicológicosunclassified